INTEGRASI BUDIDAYA BAWANG MERAH DAN TERNAK SAPI DI DESA WATUKALANGKARI, BOMBANA - Gusnawaty HS; M. Taufik; R. Aka, K.Amartani; M. Botek (Fakultas Pertanian, 2025)
Shallots are a highly economical agricultural commodity to develop due to their numerous benefits, including their role as a highly sought-after kitchen spice. Similarly, cattle farming is also a key component. Watukalangkari Village, a village in Bombana Regency, boasts significant natural and human resource potential for shallot cultivation and livestock farming, particularly cattle farming. However, both shallot and cattle farming have not been optimally developed, resulting in lower productivity. Therefore, this initiative aims to provide technical guidance on integrating shallot cultivation management with cattle farming. The implementation method for this community service is through counseling and technical guidance on integrating shallot cultivation management with cattle farming. The implementation team has provided technical guidance to target partners in the form of a pilot project integrating shallot cultivation management with cattle farming. By integrating the shallot cultivation management system with cattle farming, target partners can address the problem of fertilizer shortages for shallot planting, reduce the negative impacts arising from free-range cattle grazing without pens, and meet the need for sufficient and more secure livestock feed.